Labor supply of older workers in Thailand: The role of co-residence, health, and pensions - Sasiwimon Warunsiri Paweenawat; Lusi Liao (Asian Development Bank Institute (ADBI), 2021)
During the last few decades, the composition of the Thai population has changed dramatically due to reduced fertility and the aging of the population. Thailand's aging society faces many challenges. This is particularly so for older Thai people who still have to work for a living due to insufficient savings. This paper first provides an overview of the basic changes related to the labor force participation (LFP) of older people using the Labor Force Survey (LFS) from 1985 to 2017. Then, this study uses Socio-Economic Survey (SES) panel data from 2005 to 2012 and employs the fixed-effect logit model (FE-logit) to estimate the determinants of older people's LFP. Our main findings provide strong evidence that pensions and poorer health status reduce the LFP of older people in Thailand. Furthermore, while health status is significant across all analyses, pensions have less impact on lower-status workers, indicating that even if they receive a pension, they may still be too poor to retire. Finally, co-residence decreases the LFP only of older people in rural areas. Those who are older, with a primary education, and who are usually employed in the informal sector suffer from poverty and require more assistance from others.
Keywords: J21; J22; J14; O17; O53; 330; population aging; older worker; elderly labor supply; Thailand